Freedom eaudiobook Memoirs 1954 – 2021. - Merkel, Angela (Macmillan Audio, 2024)
The long-awaited memoir by one of the most important political leaders of our time For 16 years, Angela Merkel bore the governmental responsibility for Germany, leading the country through numerous crises and shaping German and international politics and society with her actions and attitude. But Angela Merkel was not born a Chancellor. In her memoirs, co-written with her long-standing political advisor Beate Baumann, she looks back on her life in two German states – 35 years in the GDR (German Democratic Republic), 35 years in reunified Germany. More personally than ever before, she talks about her childhood, youth, and her studies in the GDR, and the dramatic year of 1989, when the Wall fell and her political life began. She shares insights into her meetings and conversations with the world's most powerful leaders and elucidates, with clear and precise examples, significant national, European, and international turning points and how decisions were made that shape our times. Her book offers a unique insight into the inner workings of power – and is a decisive plea for freedom. "What does freedom mean to me? This question has occupied me my entire life. Naturally, politically, because freedom needs democratic conditions, without democracy there is no freedom, no rule of law, no protection of human rights. But this question also occupies me on another level. Freedom, for me, is finding out where my own limits are, and pushing my own limits. Freedom is for me not to stop learning, not to have to stand still but to be allowed to continue, even after leaving politics." - Angela Merkel A Macmillan Audio production from St. Martin's Press.